The Effect Of Income And Financial Literacy On Investment Decisions With Financial Behavior As An Intervening Variable - M. Primastuti Dyah Shintawati; I Gusti Agung Musa Budidarma (GoAcademica Research & Publishing, 2023)
The goal of this study is to examine and demonstrate the impact of income and financial literacy on investment decisions using financial behavior as an intervening variable. The quantitative research method was applied in this investigation. This study's population consists of Micro and Small Enterprises in Yogyakarta's Special Region. The data collection method uses a questionnaire. The analysis technique in this study uses Partial Least Square (PLS). The findings of this study reveal that income, financial knowledge, and financial behavior all have an impact on investment decisions. Financial literacy has an impact on financial conduct, whereas income has no impact on financial behavior. Meanwhile, financial conduct can mitigate the impact of financial literacy on investment decisions, but it cannot mitigate the impact of income on investment decisions.